TEORI PENELITIAN KUALITATIF - Annisa Qurratul Aini Annisa; Zamsiswaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Qualitative research is a research approach aimed at understanding social phenomena in depth through the exploration of meanings, experiences, and perspectives of individuals or groups. This study aims to examine the concept of theory in qualitative research and the role of theory in the research process. The method used in this study is a qualitative approach with a library research design. Data were obtained from various sources such as books, scientific journals, and other relevant literature related to qualitative research theory. Data collection techniques were carried out through documentation by reading, reviewing, and analyzing various sources related to qualitative research theory. The data were analyzed using descriptive qualitative analysis to explain the concepts and roles of theory in qualitative research. The results of the study indicate that theory in qualitative research has a flexible role and can be used at various stages of research, namely as an initial lens (prefigured theory), as a theory emerging from data (grounded theory), and as a final reflection on research findings. Therefore, broad theoretical knowledge is essential for qualitative researchers in order to understand phenomena deeply and produce systematic and meaningful research.